Direct Printing of Micropatterned Plasmonic Substrates of Size‐Controlled Gold Nanoparticles by Precision Photoreduction. Issue 1 (29th October 2020) - Zhang, Yangxi; Liang, Zengtian; Zhang, A. Ping; Tam, Hwa‐Yaw
Abstract: Although the extraordinary optical property of gold nanoparticles (AuNPs) has been known for a long time, the anticipated applications of AuNPs in plasmonically enhanced substrates and photonic microdevices are still under development. In this paper, a method for the direct printing of micrometer‐scale patterns of size‐controlled AuNPs is presented for plasmonic substrates and microsensor development. Using in‐house digital ultraviolet lithography, a precision photoreduction technology is developed for light‐controlled growth of AuNPs to create micrometer‐scale micropatterns on a titanium dioxide photocatalytic layer. The titanium dioxide thin layer not only enables a photocatalytic reduction process for high‐precision printing of size‐controlled AuNPs in an additive manner, but also introduces a Fano resonance that can sharpen spectral width of localized surface plasmon resonance peak and increase its peak‐to‐valley value. This printing technology can be used to cost‐effectively fabricate size‐scalable micropatterned plasmonic substrates of size‐controlled AuNPs and thus offers new opportunities to develop various types of miniature plasmonic devices ranging from plasmonic biochemical sensors to plasmonically enhanced photothermal and photovoltaic microdevices. Abstract : A method for the direct printing of micropatterns of size‐controlled gold nanoparticles (AuNPs) is presented. A precision photoreduction technology is developed for light‐controlled growth of AuNPs to create micrometer‐scale micropatterns on a titanium dioxide photocatalytic layer. This printing technology offers new opportunities to develop various miniature plasmonic devices ranging from plasmonic biosensors to plasmonically enhanced photothermal and photovoltaic applications.